Ecological Momentary Assessment of Alcohol Consumption and Its Concordance with Transdermal Alcohol Detection and Timeline Follow‐Back Self‐report Among Adults Experiencing Homelessness. (3rd March 2021) - Mun, Eun‐Young; Li, Xiaoyin; Businelle, Michael S.; Hébert, Emily T.; Tan, Zhengqi; Barnett, Nancy P.; Walters, Scott T.
Abstract : Background: Studies of alcohol use presume valid assessment measures. To evaluate this presumption, we examined the concordance of alcohol use as measured by ecological momentary assessment (EMA) self‐reports, transdermal alcohol concentration readings via the Secure Continuous Remote Alcohol Monitor (SCRAM), and retrospective self‐reports via the Timeline Follow‐Back (TLFB) among adults experiencing homelessness. Methods: Forty‐nine adults who reported alcohol misuse (mean age = 47, SD = 9; 57% Black; 82% men) were recruited from a homeless shelter. For 4 weeks, alcohol use was assessed: (i) 5 times or more per day by EMA, (ii) every 30 minutes by a SCRAM device worn on the ankle, and (iii) by TLFB for the past month at the end of the study period. There were 1, 389 days of observations of alcohol use and alcohol use intensity for 49 participants. Results: EMA and SCRAM alcohol use data agreed on 73% of days, with an interrater agreement Kappa = 0.46. A multilevel analysis of concordance of 3 measures for alcohol use yielded statistically significant correlations of 0.40 (day level) and 0.63 (person level) between EMA and SCRAM. Alcohol use was detected on 49, 38, and 33% of days by EMA, SCRAM, and TLFB, respectively. For alcohol use intensity, EMA and SCRAM resulted in statistically significant correlations of 0.46 (day level) and 0.78 (person level). The concordance of TLFB with either EMA or SCRAM was weak, especially at the day level. Conclusions: This is the first study to examine concordance of alcohol use estimates using EMA, SCRAM, and TLFB methods in adults experiencing homelessness. EMA is a valid approach to quantifying alcohol use, especially given its relatively low cost, low participant burden, and ease of use. Furthermore, any stigma associated with wearing the SCRAM or reporting alcohol use in person may be attenuated by using EMA, which may be appealing for use in studies of stigmatized and underserved populations. Abstract : We examined concordance of alcohol use as measured by ecological momentary assessment (EMA) self‐reports, transdermal alcohol concentration readings via the Secure Continuous Remote Alcohol Monitor (SCRAM), and retrospective self‐reports via the Timeline Follow‐Back (TLFB) in adults experiencing homelessness. The concordance between EMA and SCRAM was promising while the concordance of TLFB with either EMA or SCRAM was weak. EMA for alcohol consumption is valid and encouraging, given its relatively low cost, low participant burden, ease of use, and less stigma.